2018
DOI: 10.1051/matecconf/201816515001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of notch effects in low cycle fatigue of alloy 718 using critical distances

Abstract: Abstract. Gas turbine disks contain many notch-like features acting as stress raisers. The fatigue life based on the notch root stress may be overly conservative as the steep stress gradient in front of the notch may give rise to so-called notch support. In the current work, the theory of critical distances was applied to the prediction of the total fatigue life of low cycle fatigued, notched specimens made from alloy 718. The fatigue tests were performed at 450 °C and 550 °C. It was found that, for lives shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Eriksson et al [6] demonstrated that the critical distance could also be based on the notch root plastic strain range, ∆ε root p , via a simple power law r = p ∆ε root p q (5) where p and q are fitting parameters. The rationale being that the notch root strain range correlates to the strain range further into the material.…”
Section: Theory Of Critical Distancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Eriksson et al [6] demonstrated that the critical distance could also be based on the notch root plastic strain range, ∆ε root p , via a simple power law r = p ∆ε root p q (5) where p and q are fitting parameters. The rationale being that the notch root strain range correlates to the strain range further into the material.…”
Section: Theory Of Critical Distancesmentioning
confidence: 99%
“…In the current work, the method suggested by Eriksson et al [6] will be further explored and a rationale for why the critical distance should correlate with notch root conditions will be provided. It will be shown that the critical distance can also be correlated to the notch root stress taken from a linear elastic finite element analysis (FEA).…”
Section: Theory Of Critical Distancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes, this was not even indicated, 38,39 or no comparison with a smooth specimen Wöhler curve was provided, 40 which makes it hard to judge whether a notch improves or decreases the fatigue life. However, there are publications showing that notches are improving the LCF fatigue lives of specimens, e.g., for conventionally cast or even directionally solidified Ni-base superalloys 13,41,42 and steels. 13,31,[43][44][45] Interestingly, Haibach and Matschke et al 31 observed improvements in LCF lives, but HCF strength reductions at notched steel specimens.…”
Section: Introductionmentioning
confidence: 99%
“…13,31,[43][44][45] Interestingly, Haibach and Matschke et al 31 observed improvements in LCF lives, but HCF strength reductions at notched steel specimens. Furthermore, Eriksson et al 41,46 noted that the LCF notch support at high loads changed to notch weakening at lower load amplitudes for the Nibase alloy IN-718.…”
Section: Introductionmentioning
confidence: 99%